An investigation into the accuracy of pre-tender design price forecasts provided by the quantity surveyor - Donald, Gail (Department of Construction Economics and Management, 2020)
It is the intention of this dissertation to determine the most influential factors affecting the accuracy of design · price forecasts. As a result of the lack of research relating to the accuracy design price forecasts in South Africa, quantity surveyors are unaware of the level of accuracy that they attain. It is proposed that an awareness of their forecasting accuracy.and the factors which affect will contribute towards enhanced performance. By means of an analysis of a sample of quantity surveyors estimates, the factors which exert the most significant influence over identified.